2018
DOI: 10.1039/c7ee02874a
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of sulfur cathodes: new insights into Li–S batteries via operando X-ray based methods

Abstract: For Li–S batteries, operando X-ray diffraction and X-ray microscopy are combined to visualize the evolution of both the morphology and crystal structure of the materials during the cycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 30 publications
5
123
0
Order By: Relevance
“…11 These materials can be studied in a host of different experimental or real conditions; these range from post-mortem analysis of degradation or failure mechanisms, [12][13][14][15] to mechanistic studies through in situ and operando measurements. [16][17][18][19] Valuable metrics such as porosity, pore and particle size distributions, and tortuosity can be extracted directly from the volumetric image data, serving as a diagnostic tool that offers a deeper insight into performance limitations and degradation pathways leading to failure. More recently, the availability of greater computing power has facilitated the use of actual image data to build more realistic models of battery systems.…”
Section: Introductionmentioning
confidence: 99%
“…11 These materials can be studied in a host of different experimental or real conditions; these range from post-mortem analysis of degradation or failure mechanisms, [12][13][14][15] to mechanistic studies through in situ and operando measurements. [16][17][18][19] Valuable metrics such as porosity, pore and particle size distributions, and tortuosity can be extracted directly from the volumetric image data, serving as a diagnostic tool that offers a deeper insight into performance limitations and degradation pathways leading to failure. More recently, the availability of greater computing power has facilitated the use of actual image data to build more realistic models of battery systems.…”
Section: Introductionmentioning
confidence: 99%
“…[75][76][77] Furthermore, the presence of electrocatalysts can dynamically influence the nucleation and growth of Li 2 S, feasibly presenting a route toward addressing the detrimental growth mechanisms shown by Abruña and co-workers. [72] In 2016, Zhu et al demonstrated a nitrogen-enriched carbon host, which allowed the sulfur active material to outperform an unmodified carbon host at low temperatures. [78] Indeed, after 100 cycles at −20 °C, the nitrogen-enriched cathode demonstrated a discharge capacity of 368 mA h g −1 , compared to just 115 mA h g −1 for the unmodified cathode.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…These results support that the ECI process leads to homogeneous sulfur dispersion covering even the pores of MCN, which is believed to be helpful to the cycle stability and rate performance. [19] Battery performance tests were conducted with the two electrodes. Before the ECI process, the melt electrode has higher sulfur-carbon contact area, resulting in higher capacity than that of the mix electrode (Figure 4a).…”
Section: Enhancing the Of Performance Of Lithium-sulfur Batteries Thrmentioning
confidence: 99%